CRISPR/Cas9 Targeted Gene Editing and Cellular Engineering in Fanconi Anemia - Osborn, Mark J. (Stem Cells Dev, 2016)
The ability to rationally target disease-causing mutations has been made possible with programmable nucleases with the clustered, regularly interspaced short palindromic repeats/Cas9 system representing a facile platform for individualized gene-based medicine. In this study we employed footprint-free reprogramming of fibroblasts from a patient with mutations to the Fanconi anemia I (FANCI) gene to generate induced pluripotent stem cells (iPSCs). This process was accomplished without gene complementation and the resultant iPSCs were able to be gene corrected in a robust manner using the Cas9 nickase. The self-renewing iPSCs that were maintained under feeder-free conditions were differentiated into cells with characteristics of definitive hematopoiesis. This defined and highly efficient procedure employed small molecule modulation of the hematopoietic differentiation pathway and a vascular induction technique to generate hematopoietic progenitors. In sum, our results demonstrate the ability to induce patient-derived FA cells to pluripotency for patient-specific therapeutic cell derivation.